TVT or TVT-O? – A systematic review and meta-analysis comparing efficacy, complications and re-operations. (March 2021) - Elers, Jimmi; Hornum Bing, Mette; Birkefoss, Kirsten; Rohde, Jeanett Friis; Ussing, Anja; Glavind, Karin
Highlights: Patients in need of surgical treatment with a mid-urethral sling for SUI should be offered a TVT procedure to avoid procedure related groin pain. Abstract: Objectives: To compare the efficacy, complications and re-operations after bottom-up tension-free vaginal tape (TVT) and inside-out tension-free vaginal tape - obturator (TVT-O) in the treatment of stress urinary incontinence (SUI) in adult women. Study design: A systematic literature search and review was performed limited to randomized controlled trials. We searched Medline, Embase, Cochrane Library, Cinahl, Guideline International network (GIN), Trip Database and NICE (UK). The certainty in the estimates of the included outcomes was rated using the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) method. Results and conclusions: We included 22 randomized controlled trials. The overall certainty in the evidence was moderate across all outcomes. TVT and TVT-O significantly improved the incontinence regarding number of incontinence episodes, subjective patient reported effect and incontinence related quality of life, and there was no difference between TVT and TVT-O. Leg or groin pain was significantly less common 6 months after TVT than TVT-O with RR 0.27 (CI 95 % 0.11 – 0.66), 9 studies, n = 1312. In absolute numbers 83 patients more developed chronic leg or groin pain per 1000 operations with TVT-O compared to TVT. We found no statistically significant differences between chronic pelvic or lower abdominal pain 6 months after TVT and TVT-O. Bladder perforations were significantly more common after TVT with RR 4.53 (CI 95 % 2.32–8.86), 21 studies, n = 3308. In absolute numbers this meant 5 more bladder perforations after TVT per 1000 operations. No statistically significant differences were noted in de novo urgency, re-operations, infection, hematoma, pain during sexual intercourse or sexual function. Bottom-up TVT and inside-out TVT-O showed equal efficacy, but leg and groin pain were much more common with TVT-O. The authors would recommend TVT instead of TVT-O as first line operation in patients who need surgery for SUI.